Vegetation transitions drive the autotrophy-heterotrophy balance in Arctic lakes - McGowan, Suzanne; Anderson, N. John; Edwards, Mary E.; Hopla, Emma; Jones, Viv; Langdon, Pete G.; Law, Antonia; Soloveiva, Nadia; Turner, Simon; van Hardenbroek, Maarten; Whiteford, Erika J.; Wiik, Emma (Wiley Open Access, 2018)
“Arctic greening” will alter vegetation quantity and quality in northern watersheds, with possible consequences for lake metabolic balance. We used paleolimnology from six Arctic lakes in Greenland, Norway, and Alaska to develop a conceptual model describing how climate-driven shifts in terrestrial vegetation (spanning herb to boreal forest) influence lake autotrophic biomass (as chlorophyll and carotenoid pigments). Major autotrophic transitions occurred, including (1) optimal production of siliceous algae and cyanobacteria/chlorophytes at intermediate vegetation cover (dwarf shrub and Betula; dissolved organic carbon (DOC) range of 2–4 mg L-1), below and above which UVR exposure (DOC;<2 mgL-1) and light extinction (DOC;>4 mgL-1), respectively limit algal biomass, (2) an increase in potentially mixotrophic cryptophytes with higher forest cover and allochthonous carbon supply. Vegetation cover appears to influence lake autotrophs by changing influx of (colored) dissolved organic matter which has multiple interacting roles—as a photoprotectant—in light attenuation and in macronutrient (carbon, nitrogen) supply.